Health care of deaf persons during coronavirus pandemics - Luana Paula de Figueiredo Correia; Márcia de Assunção Ferreira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To reflect about the barriers experienced by the deaf population during the COVID-19 pandemic, the proposals to overcome communication barriers in health care and the role of public policies in effecting the social inclusion of deaf people. Methods: Reflection based on studies on health care for deaf people, the COVID-19 pandemic and public accessibility policies. Results: The global crisis of COVID-19 has deepened pre-existing inequalities in the world, in addition to highlighting the vulnerability of people with disabilities, including deaf. Government, institutional and social initiatives to mitigate difficulties in communicating to deaf people have been made, but they are still insufficient to guarantee protection for them in this pandemic and full inclusion in health care. Final considerations: Social inclusion, supported by law, and the linguistic accessibility of deaf people still need to generate broad and concrete actions so that deaf people can enjoy their rights as citizens.